Burnout Syndrome Among Hospital Healthcare Workers During the COVID-19 Pandemic and Civil War: A Cross-Sectional Study - Elhadi, Muhammed; Msherghi, Ahmed; Elgzairi, Moutaz; Alhashimi, Ayiman; Bouhuwaish, Ahmad; Biala, Marwa; Abuelmeda, Seraj; Khel, Samer; Khaled, Ala; Alsoufi, Ahmed; Elmabrouk, Amna; Alshiteewi, Fatimah Bin; et al. (Frontiers in Psychiatry, 2020)
Objective We aimed to determine the prevalence of burnout among hospital healthcare workers in Libya during the coronavirus disease (COVID-19) pandemic and civil war. Methods A cross-sectional study was conducted from April 18 to May 2, 2020 among Libyan healthcare workers. Data on participant characteristics were collected with a specifically designed questionnaire. Burnout was assessed with the abbreviated Maslach Burnout Inventory (aMBI) comprising three subscales: emotional exhaustion (EE), depersonalization (DP), and personal accomplishment (PA), with each sub-scale score range from 0 to 18. For EE and DP, scores of 10 to 18 were regarded as “moderate to severe burnout.” PA was scored inversely, where a score ≤10 indicated severe burnout. Results The study yielded a sample size of 532 participants. Of these, 357 (67.1%) reported emotional exhaustion (EE Score 10), 252 (47.4%) reported depersonalization (DP score, and 121 (22.7%) reported a lower sense of personal accomplishment (PA score 10). Verbal abuse was experienced by 304 participants (57.1%) and physical abuse in 93 (17.5). Gender was associated with high emotional exhaustion and high depersonalization. Being 35 years or older was associated with high depersonalization. Professional specialty was significantly associated with high emotional exhaustion and depersonalization. Fear of COVID-19 infection was associated with high emotional exhaustion and high depersonalization. Conclusion The rising prevalence of mental disorders and inadequate availability of health services facilities during the COVID-19 pandemic and civil war demonstrated the need for healthcare policies to address the well-being of healthcare workers to decrease the risk of loss, suicide, and medical negligence.